Development of methods to improve the technology of reproduction of lemon (Citrus limon L.) by green cuttings - Kazakov Pavel; Ter-Petrosyants Georg; Akimova Svetlana; Marchenko Ludmila; Zubkov Alexander (BIO Web of Conferences)
The paper studies the effect of the form of preparation (powder and alcohol solution) and concentrations of auxin class phytohormone - indolyl-3- butyric acid (IBA) on morphometric parameters of root system development in green lemon cuttings at rooting under conditions of fog. The results of the study showed 100% rooting of Meyer lemon (C. meyeri) in all variants, and also revealed the advantage of using rooting powder with a concentration of 0.75% IBA. At rooting of ‘Novogruzinsky’ lemon variety (Citrus limon L.) 100% rooting ability was detected in all variants except for alcohol solution with concentration of 1.0%. According to the indicators of root system development the advantage of rooting powder with IBA concentration 1.0% and alcohol solution with IBA concentration 0.75% was revealed.